Pengembangan E-LKPD Berbasis Model Treffinger pada Materi Trigonometri - Exzanti, Averta; Mawardi, Dona Ningrum; Mulyono, Dodik (Papanda, 2025)
This study aims to develop an e-worksheet (E-LKPD) based on the Treffinger model for trigonometry material in Grade X at SMK Yadika Lubuklinggau that meets the criteria of validity, practicality, and effectiveness. The research method used is the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation) with a Research and Development (R&D) approach. Data collection techniques involved interviews, questionnaires, and tests. The research instruments included validation questionnaires (for material, language, and media experts), practicality questionnaires (for teachers and students), and learning outcome tests. The data were analyzed both qualitatively and quantitatively to assess the product’s validity, practicality, and effectiveness. The results showed that the developed E-LKPD had a very high level of validity, was considered highly practical, and achieved good effectiveness. Therefore, the Treffinger-based E-LKPD is deemed suitable for use in mathematics learning on trigonometry material.